Akuntabilitas Kinerja, Keamanan Dan Jam Kerja Terhadap Produktivitas Kerja Anggota Satbrimob Batalyon B Pelopor PMJ Cipinang Dimediasi Disiplin Kerja - Dwi Putri Aprillia; Dewi Puspaningtyas Faeni; Novita Wahyu Setyawati (Asosiasi Riset Ilmu Manajemen Kewirausahaan dan Bisnis Indonesia, 2024)
This study aims to determine Performance Accountability, Security and Working Hours on Work Productivity of Members of Satbrimob B Battalion B Pioneer PMJ Cipinang through (mediated) Work Discipline. This research method is descriptive quantitative type by distributing questionnaires (Likert scale 1-5) to a sample size of 83 out of 500 respondents calculated by the Slovin formula and processed with SmartPLS 3.2.9 software. The results showed that the path coefficient and p-value of the Performance Accountability variable (0.228 and 0.005), Security (0.062 and 0.062), and Working Hours (0.226 and 0.007). This means that Performance Accountability and Working Hours partially have a significant positive effect on the Work Productivity of Members of Satbrimob B Battalion B Pioneer PMJ Cipinang through (mediated) Work Discipline. While Security partially has no effect on the Work Productivity of Members of Satbrimob Battalion B Pioneer PMJ Cipinang through (mediated) Work Discipline. Furthermore, the path coefficient and p-value of the Work Discipline variable are 0.410 and 0.002. This means that work discipline has a significant positive effect on the work productivity of members of Satbrimob Battalion B Pioneer PMJ Cipinang.